2018
DOI: 10.1186/s13071-018-2895-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum msp1 and msp2 genetic diversity and allele frequencies in parasites isolated from symptomatic malaria patients in Bobo-Dioulasso, Burkina Faso

Abstract: BackgroundIn Burkina Faso, malaria remains the overall leading cause of morbidity and mortality accounting for 35.12% of consultations, 40.83% of hospitalizations and 37.5% of deaths. Genotyping of malaria parasite populations remains an important tool to determine the types and number of parasite clones in an infection. The present study aimed to evaluate the merozoite surface protein 1 (msp1) and merozoite surface protein 2 (msp2) genetic diversity and allele frequencies in Bobo-Dioulasso, Burkina Faso.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
64
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 42 publications
22
64
4
1
Order By: Relevance
“…In this study, 80% of the isolates harboured more than one parasite genotype identi ed by the presence of two or more alleles of one or both genes with the overall mean MOI being 3.2 (95% CI: 2.87-3.46). The overall MOI value reported in this study was higher than previously reported studies, including Ethiopia (MOI: 1.8 -2.6) between 2015-2018 [42,43,44], Brazzaville, Republic of Congo (MOI: 2.2) [16] in 2011 and Bobo-Dioulasso, Burkina Faso (MOI: 1.95) [62]. In contrast to study reported in Bioko Island, Equatorial Guinea (MOI: 5.51) [53] in 2018 and Gabon (MOI: 4.0) [63] in 2018.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, 80% of the isolates harboured more than one parasite genotype identi ed by the presence of two or more alleles of one or both genes with the overall mean MOI being 3.2 (95% CI: 2.87-3.46). The overall MOI value reported in this study was higher than previously reported studies, including Ethiopia (MOI: 1.8 -2.6) between 2015-2018 [42,43,44], Brazzaville, Republic of Congo (MOI: 2.2) [16] in 2011 and Bobo-Dioulasso, Burkina Faso (MOI: 1.95) [62]. In contrast to study reported in Bioko Island, Equatorial Guinea (MOI: 5.51) [53] in 2018 and Gabon (MOI: 4.0) [63] in 2018.…”
Section: Discussioncontrasting
confidence: 78%
“…On the whole, we found that about 65% of the study participants had polyclonal infections consisting of 2-6 clones with an overall MOI of 2.31 clones per infected child. This observation was not different from our previous report [31] and is also consistent with other data from Nigeria [40,41] and from other parts of Africa [14,24,[42][43][44][45][46][47][48][49][50]. The simultaneous infection of large number of individuals with multiple parasite genotypes in areas of high transmission intensity has been suggested to be attributable to either multiple inoculations of single clones, or by a single inoculation of multiple clones that may have undergone crossing and recombination in the female Anopheles mosquito vector [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…Because the characterization of vector competence for oocyst and sporozoite stages partly relied on different gametocyte carriers (Table 1), such isolate-dependent effect of irradiation could also explain why, on average, the sporozoite infection rate of irradiated individuals was not significantly lower than that of unirradiated-control individuals (Figure 1C). Here, we used wild parasite isolates from a geographic area characterized by an important genetic diversity (Somé et al ., 2018). Accordingly, some parasite clones might perform well in irradiated mosquitoes while others would be more infective to non-irradiated mosquitoes.…”
Section: Discussionmentioning
confidence: 99%